2009
DOI: 10.2353/ajpath.2009.080953
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Activated STAT5 in Neoplastic Mast Cells in Systemic Mastocytosis

Abstract: Recent data suggest that the signal transducer and activator of transcription (STAT)5 contributes to differentiation and growth of mast cells. It has also been described that constitutively phosphorylated STAT5 (pSTAT5) plays a pro-oncogenic role in various myeloid neoplasms. We examined the expression of pSTAT5 in neoplastic mast cells in systemic mastocytosis and asked whether the disease-related oncoprotein KIT D816V is involved in STAT5 activation. As assessed by immunohistochemistry using the anti-pSTAT5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…Previous studies showed that in neoplastic mast cells and in leukemia KIT D816H mutations lead to STAT3 and STAT5 activation [2931]. We found similar changes in STAT signaling using melanocytes strongly suggesting a distinct effect of the KIT mutation rather than a cell specific change.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies showed that in neoplastic mast cells and in leukemia KIT D816H mutations lead to STAT3 and STAT5 activation [2931]. We found similar changes in STAT signaling using melanocytes strongly suggesting a distinct effect of the KIT mutation rather than a cell specific change.…”
Section: Discussionsupporting
confidence: 77%
“…Active Stat5 is thought to play an essential role in regulating the transformation of FLT3 and KIT oncogene bearing cells (Baumgartner et al, 2009; Brady et al, 2012). Although Stat5 is a transcription factor, mechanism(s) involved in the transport of this molecule in and out of the nucleus in oncogene bearing cells remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of phosphorylated (p) pStat5 in newly diagnosed AML patients is also associated with poor overall survival (Brady et al, 2012). Constitutive activation of pStat5 is observed in 100% of systemic mastocytosis (SM) patients bearing the KITD816V mutation (Baumgartner et al, 2009). A strong correlation between the presence of pStat5 and FLT3ITD mutations is seen in AML patients and FLT3ITD expression results in constitutive Stat5 phosphorylation (Obermann et al, 2010) (Spiekermann et al, 2003), (Choudhary et al, 2007; Choudhary et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…95 Clinically, neoplastic mast cells in SM patients have been shown to unanimously express elevated levels of phosphorylated STAT5 found in both the cytoplasm and the nucleus of mast cells, an effect that was attributed to D816V c-kit signaling and blunted by inhibition of D816V kinase activity. 101 …”
Section: Jaks and Stats In Mastocytosismentioning
confidence: 99%